2019
DOI: 10.4049/jimmunol.1801108
|View full text |Cite
|
Sign up to set email alerts
|

The Cross-Talk between miR-511-3p and C-Type Lectin Receptors on Dendritic Cells Affects Dendritic Cell Function

Abstract: MicroRNAs are small, noncoding RNAs that function as posttranscriptional modulators of gene expression by binding target mRNAs and inhibiting translation. They are therefore crucial regulators of several biological as well as immunological events. Recently, miR-511-3p has been implicated in the development and differentiation of APCs, such as dendritic cells (DCs), and regulating several human diseases. Interestingly, miR-511-3p is embedded within the human MRC1 gene that encodes the mannose receptor. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 58 publications
3
14
1
Order By: Relevance
“…the level of PPARγ relative to miR-511-3p) indicated by an increase in PPARγ expression when miR-511-3p is low and vice versa, when miR-511-3p expression is high. It is important to note that transfection with either miR-511-3p inhibitors or mimics did not result in loss of cell viability as determined by Annexin-V staining (Figure S1) and did not impact monocyte to DC differentiation as we have previously demonstrated (24).…”
Section: Resultssupporting
confidence: 56%
“…the level of PPARγ relative to miR-511-3p) indicated by an increase in PPARγ expression when miR-511-3p is low and vice versa, when miR-511-3p expression is high. It is important to note that transfection with either miR-511-3p inhibitors or mimics did not result in loss of cell viability as determined by Annexin-V staining (Figure S1) and did not impact monocyte to DC differentiation as we have previously demonstrated (24).…”
Section: Resultssupporting
confidence: 56%
“…In this study, we have provided evidence that the increased AHR and lung inflammation due to the lack of Mrc1 can be reversed by AAV-mediated transduction of miR-511-3p. Furthermore, by gene array analysis, we have iden- the regulation of intestinal inflammation (20), and affects DC function by cross-talk with CLRs (21). Recent studies have also suggested that miR-511-3p may be a prognostic factor and potential tumor suppressor through inverse regulation of its downstream target gene AKT (serine/threonine-specific protein kinase 3) (34).…”
Section: Discussionmentioning
confidence: 99%
“…miR-511-3p is transcriptionally coregulated with the MRC1 gene in macrophages (10,19). Recent studies have suggested that miR-511-3p controls the activation of tumor-associated macrophages (19), regulates intestinal inflammation by targeting Toll-like receptor 4 (TLR4) (20), and affects dendritic cell (DC) function by cross-talk with CLRs (21). Profiling of macrophages demonstrated opposing expression patterns for miR-511 in M1 and M2 macrophages, with an increased expression of miR-511-3p in M2, but decreased expression in M1 macrophages (22).…”
Section: Introductionmentioning
confidence: 99%
“…miR‐511‐3p was also reported to be implicated in the development and differentiation of DCs. A recent study by Awuah et al 17 revealed that miR‐511‐3p could modulate immunogenicity of DCs through regulating the expression of mannose receptor and DC‐specific ICAM 3 nonintegrin. miR‐511‐3p knockdown induced an anti‐inflammatory DC response and promoted immune suppression.…”
Section: Discussionmentioning
confidence: 99%